An overview of sexual assault survivors: a 5 year retrospective study in gynaecology department of NSCB medical college, Jabalpur, Madhya Pradesh, India - Rawat, Sarika; Guin, Gita; Dadich, Ruchita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Rape and abuse of women are common occurrences, which many times go unreported due to social stigma or fear of retribution. Rape is a crime not against a single human being but against the entire humanity. For granting justice to the rape survivor, it becomes necessary that such matters are properly presented before the Courts of Law. Healthcare workers play an important role in this regard because they are the first people who examine the survivors. They document record of the history and medical condition of the survivor and do relevant sample collection. The objective of this study is to analyze demographic and event characteristics of rape survivors who presented to the gynecology department of Government NSCB MCH, Jabalpur with history of sexual assault. Methods: Data was retrospectively collected from the medico legal records of the department of Gynecology between April 2013 to March 2018. Results: An increase in number of cases of sexual assault reporting to the hospital every year is observed. Age wise distribution showed that 27.66% cases were in age group 6-10 years and 16-20years being the major affected group. Majority of the cases belonged to low socio-economic strata. 91.5% survivors were unmarried. 61.7% of the survivors were from rural areas. 44.7% of survivors reported within a day of the incident and most of the assailants were known to the survivors; only 36.2 % were strangers. Most of the incidences (23.4%) took place in the assailant’s house and survivors house each. In 31.9% cases there was evidence of fresh hymen tear. Conclusions: An understanding of the demography of sexual assault survivors will help us to better train our doctors in proper attitude and handling of such cases, an area often neglected.